Awake Prone Positioning In COVID Positive Patients: A Retrospective Study - Dangol, Shova; Poudel, Dipesh; Shrestha, Surendra Man; Rawal, Prabhat; Shrestha, Kundu (Journal of Nepal Health Research Council, 2024)
Background: While the advanced health care settings are struggling hard to handle the sudden surge of COVID-19 cases, resource poor settings in developing countries like Nepal can barely stand to fight the increasing number of severe cases. Easily available cost effective interventions would be great blessing for such settings. This study aimed to study if awake prone positioning can be used as such intervention in COVID 19. Methods: The retrospective study involved 150 patients admitted between November 2020 and January 2021 at Nepal Armed Police Force Hospital and met specific inclusion criteria. Data was obtained at four different time points in relation to prone position and was analysed using International Business Machines Statistical Package for the Social Sciences (SPSS) version 23. Results: It was found that among 150 patients, majority (109; 72.7%) were males and 60(40%) had some comorbidities. The mean oxygen saturation was found to increase significantly from 87.18 %(SD 3.531) to 91.08(SD 2.206) after fifteen minutes of prone positioning. One way ANOVA test showed that there was significant difference in oxygen saturation between at least two time points. (F (3,596) = [180.005], p=0.000). Games Howell Post Hoc test for multiple comparisons showed that the mean value of SPO2 was significantly different across all four time points, at significance level 0.05. Conclusions: This study found Awake Prone positioning as a promising cost effective and feasible intervention for improving oxygenation in COVID 19 and thus could be a blessing to the resource poor health care settings. Keywords: Awake prone; COVID-19; oxygen saturation; resource-poor.